Impact of Organizational Dehumanization on Employee Knowledge Hiding - Rubbab, Um E.; Khattak, Sana Aroos; Shahab, Hina; Akhter, Naveed (Frontiers in Psychology, 2022)
Knowledge hiding has become an alarming issue for the organizations. Knowledge hiding is an employees’ intentional attempt to conceal knowledge requested by others at the workplace. Employee knowledge hiding significantly influences an organizations’ effective functioning. This research is an attempt to extend previous work on antecedents of knowledge hiding. Drawing on conservation of resources theory, it is proposed that receiving poor treatment by organizations in the form of organizational dehumanization creates psychological distress among employees towards the organization. Distress among workers in turn intervenes the path and increases the likelihood of engaging in knowledge hiding behaviors. Employees’ felt obligation for constructive change may moderate the relationship between organizational dehumanization and employee psychological distress. Data for the current study were collected from 245 employees of the telecommunication sector in three-time lags. The results support the direct and indirect effect of organizational dehumanization on employee knowledge hiding behaviors through the mediation of psychological distress. The results also support the moderation of felt obligation for constructive changes between organizational dehumanization and psychological distress. Furthermore, the findings of the study may help organizational practitioners and managers about the value of effective organizational climate and practices for better organizational functioning through knowledge sharing and providing insight into undesirable repercussions of organizational dehumanization. Implications for organizations and practitioners are discussed.